2018
DOI: 10.29252/qums.12.8.59
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Play Therapy and Storytelling on the Improvement of Attention Deficit/Hyperactivity Disorder Symptoms in Students

Abstract: Background and Objectives: Attention deficit/hyperactivity disorder is associated with many problems and several treatments have been proposed for the treatment of children with this disorder. The present study was carried out with the purpose of determining the effectiveness of play therapy and storytelling on the improvement of the symptoms of hyperactivity disorder/attention deficit disorder in students. Methods:The research method was pretest and posttest design with control group. At first, the Conners sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Results of the analysis of covariance indicate that narrative therapy was effective in reducing two components of behavior problems in students; namely attention deficit and the fear. These findings were consistent with Titus & Sinacor (15), Bayat et al (16), and Yadi et al (17).…”
Section: Discussionsupporting
confidence: 92%
“…Results of the analysis of covariance indicate that narrative therapy was effective in reducing two components of behavior problems in students; namely attention deficit and the fear. These findings were consistent with Titus & Sinacor (15), Bayat et al (16), and Yadi et al (17).…”
Section: Discussionsupporting
confidence: 92%
“…Recent research had shown the effectiveness of physical activity and rhythmic exercise on memory and learning. Studies showed that there was a positive relationship between play and attention improvement, planning skills and attitudes, creativity and thought-orientation (Bayat et al, 2018), insight and language development (Orr & Geva, 2015). Ahmad et al (2016) stated that there was a strong relationship between play and cognitive development.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reasons to computers as an ideal training partner for mental development [20]. Computers facilitate the instructor's ability to customize instruction and monitor progress.…”
Section: Introductionmentioning
confidence: 99%